STUDY OF FACTORS CAUSING DELAY OF COMPLETION OF CONSTRUCTION WORK BUILDING IN AIRLANGGA UNIVERSITY SURABAYA - Bhanthara, Rangga; Mudjanarko, Sri Wiwoho; Moetriono, Hary (Inscientech: Journal of Industrial, Science and Technology, 2017)
Abstract: Delay in a construction project is a situation where a project cannot be carried out or completed on time in accordance with the planned time. This study aims to (1) knowing the factors that are causing delays in the building project at the Airlangga University in Surabaya; and (2) knowing the rank factors that are causing delays in the work on the building project at the Airlangga University. Data collected by the questionnaire survey and interview which were distributed to the respondents that experienced individuals as the executor of the project of construction of the building at Airlangga University in Surabaya or the case study projects and has held positions as leaders of the activities, the project manager or field manager, consultant supervisor or consultant construction management. Data were analyzed using methods of factor analysis and multiple linear regression analysis with SPSS for data processing. After doing regression analysis with stepwise method obtained equation Y = -3.973 + 0.489 + 0.240 X8 X7 X5 + 0.428 + 0.314 + 0.200 X1 X2 X3 + 0.185 + 0.164 + 0.102 X4 X6, it is known that (1) the labour factor (X1), design (X2), the method of implementation (X3), a substance / material (X4), finance (X5), equipment (X6), work environment (X7), and managerial (X8) affect the delay of construction work on the building Airlangga University Surabaya. (2) after multiple linear regression analysis obtained rank the(rank) the factors most dominant influence on the delay time of execution, respectively, are the factors of managerial (X8), work environment (X7), design (X2), finance (X5), labor (X1), a substance / material (X4), the method of implementation (X3), and equipment (X6). Keywords: delay factor, ranking, the method of factor analysis, multiple linear regression